Design of service robots for assistance in restaurants - Ju, Wen Bo (2019)
Singapore has been in the pressure of labour shortage in F&B service industry. Robots are used in restaurants to help ease the intensiveness of lacking human resources. However, robots are hard to integrate into restaurants. That is the reason for the Robot Integrated Restaurants being designed. Three good examples and cases were studied analysed, which guided designing the Robot integrated restaurant. The sole purpose of Robot Integrated Restaurant is to reduce human dependence in the restaurant. It also functions the same as the traditional restaurant. It solves the users need using technology and artificial intelligence. The concept of the robot integrated restaurant will be shared, and the workflow of the restaurant was described in detail. Also, the 3D model of the restaurant was designed and explained. Then one part of the restaurant-- the service robot’s 3D model was inspirited and designed. The critical feature had been described.